2022
DOI: 10.3390/brainsci12020265
|View full text |Cite
|
Sign up to set email alerts
|

Examining Association of Personality Characteristics and Neuropsychiatric Symptoms in Post-COVID Syndrome

Abstract: Background: We aimed to evaluate personality traits in patients with post-COVID syndrome, as well as the association with neuropsychiatric symptoms present in this disorder. Methods: The Big Five Structure Inventory was administered to 93 consecutive patients with a diagnosis of post-COVID syndrome as defined by the WHO and to demographically matched controls. We also performed a comprehensive evaluation of depression, anxiety, fatigue, sleep quality, cognitive function, and olfactory function. Results: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Results of other studies suggest link between semantic tasks and personality traits in AD, with particularly a higher level of openness related to better performance at similarities and verbal fluency test [ 74 ]. In COVID-19 studies personality traits are correlated with anxiety and depression, but not cognitive or olfactory function [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of other studies suggest link between semantic tasks and personality traits in AD, with particularly a higher level of openness related to better performance at similarities and verbal fluency test [ 74 ]. In COVID-19 studies personality traits are correlated with anxiety and depression, but not cognitive or olfactory function [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering depression or anxiety as a symptom of long COVID, the risk factors frequently differed among studies with contrasting results. The following patient characteristics were associated with an increased risk of depression or anxiety: personality traits, 114 female sex, 88 , 101 , 115 multimorbidity, 115 younger age. 115 In contrast, a cross‐sectional study in Egypt showed that younger age groups, 18 to 30 years old, were at lower risk of depression.…”
Section: Risk Factors Of the Neuropsychiatric Symptoms Of Long ...mentioning
confidence: 99%
“…Initial estimates suggest a prevalence of up to 43%, depending on each symptom [ 2 , 3 ]. The most common symptoms reported by patients were fatigue, dyspnea, cognitive issues, anxiety, depression, insomnia, and pain [ 4 , 5 ]. PCS is possible at all ages, but it has mainly been linked to working ages and women [ 3 ].…”
Section: Introductionmentioning
confidence: 99%